Serum cytokine levels as predictive biomarkers of benefit from ipilimumab in small cell lung cancer. (3rd June 2019) - Hardy-Werbin, Max; Rocha, Pedro; Arpi, Oriol; Taus, Álvaro; Nonell, Lara; Durán, Xavier; Villanueva, Xavier; Joseph-Pietras, Deborah; Nolan, Luke; Danson, Sarah; Griffiths, Richard; Lopez-Botet, Miguel; et al.
ABSTRACT: Background . Immunotherapy has shown efficacy in small cell lung cancer (SCLC), but only a subset of patients benefits. Surrogate biomarkers are urgently needed. Our aim was to evaluate serum Th1, Th2, and proinflammatory cytokines in two cohorts of SCLC patients before and during treatment with chemotherapy with or without ipilimumab and to correlate them with survival. Patients and methods . Two cohorts of SCLC patients were studied: patients treated with chemotherapy (n = 47), and patients treated with chemotherapy plus ipilimumab (n = 37). Baseline, on-treatment and after-treatment serum samples were evaluated for the presence of IL-1beta, IL-2, IL-4, IL-5, IL-6, IL-8, IL-10, IFN-gamma, TNF-alpha, GM-CSF, and Mip-1alpha using a Luminex assay. Differential changes in cytokines between cohorts were analyzed. Associations between cytokine levels and their changes with overall survival were evaluated. Results . Patients treated with ipilimumab showed a global increase of all cytokines after treatment initiation. A high level of IL-8 at baseline was associated with worse prognosis regardless of treatment. Baseline increased IL-2 levels predicted sensitivity to ipilimumab, while high IL-6 and TNF-alpha predicted resistance. An on-treatment increase in IL-4 levels in patients treated with immune-chemotherapy was associated with a better overall survival. Conclusions . The addition of ipilimumab to standard chemotherapy in SCLC modulates the serum levels of cytokines. Baseline levels and their change over time relate to overall survival. Blood-based biomarkers are convenient for patients, and our results support prospective validation of cytokines as predictive biomarkers for ipilimumab in SCLC.